2011
DOI: 10.1039/c1ay05107e
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting anatomical sub-structures in rat brain tissue using lipid imaging

Abstract: Cell membranes are made up of a mixture of glycerolipids, sphingolipids, gangliosides and cholesterol. Lipids play important roles in a cell’s life. However many of their functions have still to be discovered. In the present work, we describe an efficient, easy and rapid methodology to accurately localize phosphatidylcholines and sphingomyelins from a single coronal rat brain section in the cerebrum area. Matrix assisted laser desorption/ionization (MALDI) mass spectrometry was used to profile and image lipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…Delvolve et al also revealed SM (d18:1/18:0) to be distributed in the GM, and SM (d18:1/24:1) to be distributed in the WM, in rat brain sections using MALDI-LTQ-XL [38]. Even though we used a different method and animal species, our results were in good agreement with their data.…”
Section: Maldi-fticr-imssupporting
confidence: 82%
See 1 more Smart Citation
“…Delvolve et al also revealed SM (d18:1/18:0) to be distributed in the GM, and SM (d18:1/24:1) to be distributed in the WM, in rat brain sections using MALDI-LTQ-XL [38]. Even though we used a different method and animal species, our results were in good agreement with their data.…”
Section: Maldi-fticr-imssupporting
confidence: 82%
“…[29][30][31][32][33]. Several reports have shown that MALDI-IMS can be used for imaging of the sites of endogenous metabolites, especially glycerophospholipids and sphingolipids [34][35][36][37][38]. Furthermore, use of MS/MS allows the structures of imaged molecules to be identified [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…One productive approach has been to use matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) imaging in rat brain tissue sections to identify lipid species (Jackson et al, 2005a, 2005b). Subsequent studies have described discrete localization of lipids throughout both the rat (Delvolve et al, 2011; Mikawa et al, 2009) and the human brain (Veloso et al, 2011a, 2011b). These observations suggest that heterogeneity in the relative abundance of lipid species both within and between brain regions may have functional relevance.…”
Section: Introductionmentioning
confidence: 99%
“…The unique advantages of IMS include the following: (i) simultaneous detection of multiple lipids in the same specimen, which has shown that slight structural differences in lipid molecules produce a heterogeneous distribution pattern in biological tissues [13,14,[18][19][20]; (ii) application to a wide range of analytes [21], ranging from small and simple to large and more complex lipids such as glycolipids with complex oligosaccharide moieties [22,23]; (iii) a simple and fast protocol [17]. In fact, using SCI model rats, a recent study by Cooks' group found that specific lipid species accumulated in the lesion epicenter and adjacent areas after SCI [13].…”
mentioning
confidence: 99%